The efficacy of Hemospray in patients with upper gastrointestinal bleeding from tumor - Pittayanon, Rapat; Prueksapanich, Piyapan; Rerknimitr, Rungsun (Endoscopy International Open, 2016)
Background and study aims: Currently, conventional endoscopic treatments provide an unsatisfactory hemostatic outcome in upper gastrointestinal bleeding from tumor. Hemospray has been shown to be useful in many active gastrointestinal bleeding conditions. This study aimed to compare the efficacy of Hemospray and conventional endoscopic hemostasis.Patients and methods: Fourteen patients with active upper gastrointestinal bleeding from tumor were recruited. Hemospray was applied at the bleeding site until hemostasis was achieved. Four patients were excluded because they prematurely received definitive therapy to prevent further bleeding within 48 hours. Another 10 patients from historical control were matched based on the type of gastrointestinal tumors. The 14-day rebleeding rates, length of hospital stay (LOS) and mortality rate at 30-day follow up were assessed.Results: Baseline characteristics including age, stage of tumor, and Blatchford score did not differ between the two groups. The 14-day rebleeding rate in the Hemospray group was 3 times lower than the control group but not statistically significant (10 % vs. 30 %; P = 0.60). LOS was no different between the 2 groups (28.2 ± 21.2 vs. 23.8 ± 12.5 days; P = 0.26). The 30-day mortality rate in the Hemospray group was 3 times lower than that of in the conventional therapy group but not significant (10 % vs. 30 %, P = 0.7).Conclusions: Hemospray is a promising therapy for initial hemostasis in upper gastrointestinal bleeding from tumor because it can achieve hemostasis during the first 14 days, thus potentially allowing sufficient time before appropriate definitive intervention is considered.